Leadership and Challenges: A Phenomenological Exploration of Teacher-Principals in the Philippines - Melbert O. Hungo; Leomarich Casinillo; Dennis V. Madrigal (Philippine Social Science Journal, 2024)
This qualitative study employed a descriptive phenomenological approach to explore the experiences of school principals who also serve as teachers in Leyte and Southern Leyte, Philippines. Thirty school heads, selected based on experience, marital status, and willingness to participate, provided insights through a Pre-Survey form and semi-structured interviews. Thematic analysis (Colaizzi's method) revealed challenges in teaching strategies, behavior management, technology integration, and parental communication, while strategic management skills included prioritization, planning, and stress management. Findings have implications for policy development, professional development programs, and curriculum design, benefiting scholars, practitioners, and policymakers. The study highlights the unique experiences of teacher-principals, contributing to scholarly dialogue on educational leadership. Recommendations emphasize ongoing strategic management training, self-assessment, and collaborative input. By exploring innovative teaching strategies and sharing insights, teacher-principals can enhance collective educational knowledge. This study offers valuable perspectives on educational leadership, guiding policies and practices for a more effective and responsive educational system.